PEMBUATAN ALAT UKUR KELAJUAN ANGIN MENGGUNAKAN SENSOR OPTOCOUPLER DENGAN DISPLAY PC - Yanti, Nurfitriza; Yulkifli, Yulkifli; Kamus, Zulhendri (Sainstek : Jurnal Sains dan Teknologi, 2015)
The wind is one of the important parameters in meteorology to determine weather and climate. It can be determined by using two quantity measured, such us speed and direction of wind. Based on the result of measuring will obtain important information that can be used for disaster prevention. For measuring of wind speed, this reserch design a measurement using optocoupler sensor to determine wind speed with change of sensor resistance. The sensor is conected to an electronic circuit and a microcontroller Arduino Uno Rev3 and it is programmed to get the desired results. Based on data analysis, there are two result of research namely performance and design specifications. The instrument consists of two parts; the electronic circuits and mechanical parts making up the system of measuring instruments of wind speed. Based on the results conducted, the accuracy of this measuring instrument is 91.39% with 3.22% error percentage and the accuracy of the instrument was 98.9% with 1:11% relative error percentage.Key words: sensor optocoupler, microcontroler arduino